2010
DOI: 10.1016/j.jvs.2010.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on venous hemodynamics of the lower limbs

Abstract: Lower limb venous flow parameters differ significantly between healthy obese and nonobese individuals. These findings support the mechanical role of abdominal adipose tissue potentially leading to elevated risk for both venous thromboembolism and chronic venous insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 24 publications
11
97
0
9
Order By: Relevance
“…They found that there was an increase in sagittal abdominal diameter that was associated with an increase in intra-abdominal pressure more so than the waist/hip ratio. In the same line of findings, Willenberg et al 17 were able to show that lower limb venous flow parameters differ significantly between healthy obese and nonobese individuals, which supports the mechanical role of abdominal adipose tissue. In our patient population, increasing weight was not only associated with an elevated VCSS but also with other obesity-related problems such as hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 54%
“…They found that there was an increase in sagittal abdominal diameter that was associated with an increase in intra-abdominal pressure more so than the waist/hip ratio. In the same line of findings, Willenberg et al 17 were able to show that lower limb venous flow parameters differ significantly between healthy obese and nonobese individuals, which supports the mechanical role of abdominal adipose tissue. In our patient population, increasing weight was not only associated with an elevated VCSS but also with other obesity-related problems such as hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 54%
“…This means, that it is often diffi cult to relate these symptoms to a venous origin with a high certitude. Further anamnestic information such as aggravating and relieving factors, presence of risk factors for chronic venous disorder (advanced age, female sex, multiparity, positive family history of venous disease [23], obesity [24,25]), temporal or spatial relationship between the symptom and the venous pathology and exclusion of co-morbidities that can mimic (e. g. osteoarthritis or neurological conditions that can cause pain, lipoedema / lymphoedema, drugs, or congestive heart failure that can cause peripheral oedema) or produce venous symptoms (e. g. insuffi cient musculo-articular pump system) are important to increase the specifi city of these symptoms. In this sense, symptoms are generally exacerbated by heat, over the course of the day, after longer periods with the legs in a dependent position or during the premenstrual period, while they are generally relieved by elevation of the legs or by compression therapy.…”
Section: Medical Historymentioning
confidence: 99%
“…The time of the symptoms' onset is also important, since an onset in younger age should raise the suspicion of a congenital cause. Asking about recent weight changes has its relevance, because overweight has a negative impact on venous symptoms and varicose veins [24][25][26][27][28]. Beside venous symptoms and trophic changes, the presence of past or present venous complications (superfi cial vein thrombosis, variceal bleeding, venous ulceration) will infl uence the management, since they are generally indications for an active treatment [16].…”
Section: Medical Historymentioning
confidence: 99%
“…Those that do not require medical intervention are simple measures such as maintaining adequate hydration; early postoperative mobilisation; promoting healthy postoperative food intake; and encouraging healthy preoperative patient weight or BMI. 17,85,86,[94][95][96][97][98][99][100][101] Measures that involve medical intervention are mechanical prophylaxis and pharmacological prophylaxis; together these strategies tackle the sluggish blood flow and increased clotting factor levels that occur with lower limb surgery. …”
Section: Preventing Venous Thromboembolimentioning
confidence: 99%